2011
DOI: 10.1007/s10585-011-9398-4
|View full text |Cite
|
Sign up to set email alerts
|

Erlotinib inhibits osteolytic bone invasion of human non-small-cell lung cancer cell line NCI-H292

Abstract: Previous preclinical and clinical findings have suggested a potential role of epidermal growth factor receptor (EGFR) in osteoclast differentiation and the pathogenesis of bone metastasis in cancer. In this study, we investigated the effect of erlotinib, an orally active EGFR tyrosine kinase inhibitor (TKI), on the bone invasion of human non-small-cell lung cancer (NSCLC) cell line NCI-H292. First, we established a novel osteolytic bone invasion model of NCI-H292 cells which was made by inoculating cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 39 publications
5
39
0
1
Order By: Relevance
“…The current study showed that the expression of RANKL, not OPG, in osteoblasts was stimulated by EGF, and this might enhance osteoclast activation via the RANK/RANKL axis. This result is supported by previous study reported by Furugaki et al [33]. Using mouse osteolytic bone invasion model, they showed that the lung cancer cells induced RANKL expression of osteoblasts, and erlotinib inhibited the tumorinduced osteolytic invasion by suppressing osteoclast activation through inhibiting osteolytic factor production including RANKL.…”
Section: Discussionsupporting
confidence: 90%
“…The current study showed that the expression of RANKL, not OPG, in osteoblasts was stimulated by EGF, and this might enhance osteoclast activation via the RANK/RANKL axis. This result is supported by previous study reported by Furugaki et al [33]. Using mouse osteolytic bone invasion model, they showed that the lung cancer cells induced RANKL expression of osteoblasts, and erlotinib inhibited the tumorinduced osteolytic invasion by suppressing osteoclast activation through inhibiting osteolytic factor production including RANKL.…”
Section: Discussionsupporting
confidence: 90%
“…EGFR ligands stimulate osteoclast formation by inhibiting OPG expression and upregulating msRANKL 17 .…”
Section: Resultsmentioning
confidence: 99%
“…Many tumor cells with hematopoietic and epithelial origin, including colon, breast, melanoma, and non-smallcell lung cancers, were reported to directly produce IL-11 [114][115][116]. In addition, an association between an increased level of IL-11 and tumor progression was observed in different cancers, such as hepatocellular carcinoma [117], gastric carcinoma [118], pancreatic cancer [119], and renal cell carcinoma [120].…”
Section: Cancer Onset and Progressionmentioning
confidence: 99%